Role of Cr-doped NiO in reduction under a low concentration of H₂ and CO - Salma Samidin; Khairul Naim Ahmad; Mohd Razali Shamsuddin; Maratun Najiha Abu Tahari; Azizul Hakim Lahuri; Fairous Salleh; N. Asikin Mijan; Mohd Suzeren Md Jamil; Wan Nor Roslam Wan Isahak; Mohd Ambar Yarmo; Muhammad Rahimi Yusop (Elsevier B.V., 2023)
Nickel-chromium alloys are often utilized in high-resistance and heating metamaterials because of their passivity; however, their reducibility behavior has never been reported. Herein, Ni-Cr reduction has been conducted in H₂ and CO atmospheres. Nickel oxide (NiO) catalysts were impregnated with chromium and subsequently subjected to temperature-programmed reduction (TPR) at low concentrations of CO and H₂ to determine their reduction performance. The TPR profile fitting using a Gaussian function indicated the Cr-NiO reduction transformation of Cr⁶⁺→Cr³⁺ at temperatures below ~300 ◦C for both reductant gasses. Furthermore, the addition of Cr shifted the reduction peaks to a lower temperature owing to the interaction of Cr and Ni atoms, leading to increased reducibility. The characterizations of the Cr-NiO catalyst using X-ray diffraction, Brunauer–Emmet–Teller surface area, scanning electron microscopy, and X-ray photoelectron spectroscopy (XPS) analyses demonstrated the formation of NiCrxOy alloy with increasing surface area and porosity. The kinetic analysis using the Kissinger method demonstrated the reducibility of the catalysts with a low Ea value after the addition of Cr, where an Ea value of 68.0 kJ mol⁻¹ (NiO) decreased to 49.3 kJ mol⁻¹ (Cr-NiO) in the H2 atmosphere and an Ea value of 95.8 kJ mol⁻¹ (NiO) decreased to 91.9 kJ mol⁻¹ (Cr-NiO) in the CO atmosphere. The synergistic effects between Cr and Ni contributed to the increase in catalyst active sites by the transformation of the nickel oxidation state, which demonstrated the formation of oxygen vacancies and alloys, as proven via XPS analysis.